Handgun purchasing characteristics and firearm suicide risk: a nested case-control study - Julia P. Schleimer; Rose M. C. Kagawa; Hannah S. Laqueur (BMC, 2021)
Abstract Background Firearms are the most lethal method of suicide and account for approximately half of all suicide deaths nationwide. We describe associations between firearm purchasing characteristics and firearm suicide. Methods Data on all legal handgun transactions in California from 1996 to 2015 were obtained from the California Department of Justice Dealer's Record of Sale database. Handgun purchasers were linked to mortality data to identify those who died between 1996 and 2015. To account for variation in timing and duration of observation time, analyses were stratified by birth cohort. The primary analysis focused on those aged 21-25 in 1996. A secondary analysis tested associations among those aged 50-54 in 1996. Using incidence density sampling, purchasers who died by firearm suicide (cases) were each gender-matched to 5 purchasers (controls) who remained at risk at the case's time of death. We examined the characteristics of purchasers and transactions, focusing on the transaction closest in time to the case's death. Data were analyzed with conditional logistic regression. Results There were 390 firearm suicides among the younger cohort and 512 firearm suicides among the older cohort. Across both cohorts, older age at first purchase and the purchase of a revolver were associated with greater risk of firearm suicide. For example, among the younger cohort, those who purchased a revolver versus semiautomatic pistol had 1.78 times the risk of firearm suicide (95% CI 1.32, 2.40) in multivariable models. Other associations varied across cohorts, suggesting cohort or age effects in purchasing patterns. Conclusions Findings add to the evidence on firearm suicide risk and may help inform prevention strategies and future research.